2006
DOI: 10.1677/joe.1.06455
|View full text |Cite
|
Sign up to set email alerts
|

The sarcoplasmic–endoplasmic reticulum Ca2+ ATPase 2b regulates the Ca2+ transients elicited by P2Y2 activation in PC Cl3 thyroid cells

Abstract: In PC Cl3 cells, a continuous, fully differentiated rat thyroid cell line, P2Y 2 purinoceptor activation provoked a transient increase of [Ca 2C ] i , followed by a decreasing sustained phase. The a and b1 protein kinase C (PKC) inhibitor Gö 6976 decreased the rate of decrement to the basal [Ca 2C ] i level and increased the peak of Ca 2C entry of the P2Y 2 -provoked Ca 2C transients. These effects of Gö 6976 were not caused by an increased permeability of the plasma membrane, since the Mn 2C and Ba 2C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In the present study, we used PC Cl3 cells, which are differentiated thyroid cells sensitive to thyrotropin (TSH) stimulation for their growth (Fusco et al, 1987; Berlingieri et al, 1993) that express the typical markers of thyroid differentiation, such as Tg, thyroperoxidase (TPO), thyrotropin receptor (TSHR) and Na + /I − symporter (NIS). Therefore, this cell line has been used extensively for studying thyroid function, including the detailed study of the thyroid ion transporters (Marsigliante et al, 2002, 2003; Vilella et al, 2003; Ulianich et al, 2004, 2006; Verri et al, 2004). The physiology of PC Cl3 cells, as well as the expression of thyroid‐specific genes, is controlled by hormones such as TSH and insulin (Fusco et al, 1987; Kimura et al, 1999; Trapasso et al, 1999; Villone et al, 2000; Bjorklund et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used PC Cl3 cells, which are differentiated thyroid cells sensitive to thyrotropin (TSH) stimulation for their growth (Fusco et al, 1987; Berlingieri et al, 1993) that express the typical markers of thyroid differentiation, such as Tg, thyroperoxidase (TPO), thyrotropin receptor (TSHR) and Na + /I − symporter (NIS). Therefore, this cell line has been used extensively for studying thyroid function, including the detailed study of the thyroid ion transporters (Marsigliante et al, 2002, 2003; Vilella et al, 2003; Ulianich et al, 2004, 2006; Verri et al, 2004). The physiology of PC Cl3 cells, as well as the expression of thyroid‐specific genes, is controlled by hormones such as TSH and insulin (Fusco et al, 1987; Kimura et al, 1999; Trapasso et al, 1999; Villone et al, 2000; Bjorklund et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Injured cells release nucleotides that serve as ligands for cell-surface purinergic receptors, and injured neurons release components, including ATP and glutamate, that bind their respective receptors. The release of nucleotides can modulate Ca 2ϩ homeostasis (4,11,43,52,54).Neuronal transmitters such as glutamate bind to metabotropic G protein-coupled receptors or to ionotropic receptors, including 2-amino-3-(3-hydroxy-5-methyl-isoxazol-4-yl)propanoic acid (AMPA), kainate, and N-methyl-D-aspartate (NMDA) receptors. It has been reported that epithelial cells do not respond to AMPA or kainate, but they do respond to glutamate in neuronal wound media and to NMDA.…”
mentioning
confidence: 99%
“…Injured cells release nucleotides that serve as ligands for cell-surface purinergic receptors, and injured neurons release components, including ATP and glutamate, that bind their respective receptors. The release of nucleotides can modulate Ca 2ϩ homeostasis (4,11,43,52,54).…”
mentioning
confidence: 99%
“…P2YRs have been traditionally credited with growth‐promoting and we and others have shown that P2Y2 and P2Y6 receptors support cell growth in vitro (Elia et al, ; Muscella et al, ; Muscella et al, ; Wagstaff et al, ). We also observed that P2Y2 receptor plays a crucial role in different cellular responses in normal and tumorigenic thyroid cell lines (Elia et al, ; Ulianich et al, ). While P2Y expression and functions in several human tumours are well documented (Burnstock & Di Virgilio, ) no data are so far available in human MPM.…”
Section: Discussionmentioning
confidence: 69%